Novel Resistant Potato Starches on Glycemia and Satiety in Humans - Mark D. Haub; Julie A. Louk; Tara C. Lopez (Journal of Nutrition and Metabolism)
This study was designed to determine the efficacy of two novel type-four resistant starches (RS4) on postprandial glycemia and ratings of fullness. Volunteers (n=10) completed completed five interventions designed to determine the glycemic and satiety (fullness) effects of the starches (38 g,) alone and when added on top of available carbohydrate. The dose of the starches provided 30 g of resistant starch per treatment. The treatments were: commercial resistant starch added to water (PF−), noncommercial resistant starch added to water (PR−), dextrose solution (DEX, 50 g), and DEX with PenFibe starch (PF+), and DEX with the non-commercial starch added (PR+). Blood glucose was measured in the fasted state and following the randomly assigned treatments at 30, 45, 60, 90, and 120 minutes post-consumption. A visual analog scale was used to determine fullness at each time point. There were no differences in the glucose incremental areas under the curve (iAUC) for PF+ and PR+ compared with DEX. The PF− and PR− treatments had decreased (P<0.05) iAUCs for glucose compared with DEX, PF+, and PR+. There were no treatment differences for RoF. The dose (38 g) of starches did not to alter glucose responses when added on top of 50 g of dextrose.